Involvement of GABA(A)-benzodiazepine receptor in the anxiolytic effect induced by hexanic fraction of Rubus brasiliensis - Nogueira, E.; Rosa, GJM; Vassilieff, V. S. (Elsevier B.V., 1998)
To investigate the ability of hexanic ethanolic fraction of Rubus brasiliensis Martius (Roseceae), to induce anxiolytic effect and also the possible involvement of the GABA(A)-benzodiazepine receptor complex, male Wistar rats and Swiss mice behaviour were tested in the elevated plus maze (EPM). All the doses of the extract, 50, 100 and 150 mg/kg, administered per gavage (vo), 30 min before the behavioural evaluation, induced an anxiolytic effect expressed by: increased number of entries in and time spent in the open arms and percentage of open arm entries: and decreased number of entries and time spent in the closed arms. The treatment of mice with flumazenil (Ro 15-1788), 0.5, 1.0 and 1.5 mg/kg, i.p., 15-min before the administration of hexanic fraction, 100 mg/kg, vo, blocked the hexanic fraction-induced anxiolytic effect. The LD50 for the hexanic fraction was 1512 mg/kg. In conclusion, it was shown that the hexanic fraction of R. brasiliensis induced an anxiolytic effect in rats and mice. This effect can be attributed to a liposoluble principle with low toxicity which may be acting as an agonist on GABA(A)-benzodiazepine receptor complex. (C) 1998 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: Rubus brasiliensis; anxiolytic effect; elevated plus maze; GABA(A)-system; benzodiazepine receptor; rats; mice